Study on 300 t of wheat stored in corrugated steel bin for two years in Canada. Part I – Temperature and moisture profiles of the grain. (January 2023) - Bharathi, Vimala S.K.; Jian, Fuji; Jayas, Digvir S.
Abstract: Grain temperatures, moisture contents, and germination inside an un-aerated, 10 m diameter corrugated steel bin filled with 300 t of wheat with an initial moisture content of 12.5 ± 0.1% (w.b.), were monitored from September 2019 in Winnipeg, Canada. The hourly temperatures were recorded until October 2021, while moisture content and germination were monitored every month until August 2021. During the 26-month period, the temperatures inside the bin were above 7.8 °C, at least at one of the measured locations. The temperatures and the moisture contents of the grain varied with changes in ambient weather conditions. The grain moisture changes and temperature fluctuations near the surface of the bulk and temperature fluctuation near the walls were higher than those inside the grain bulk. The temperature gradient-induced convective currents and the hotspot development triggered the moisture migration inside the bin. The presence of high moisture grains (as a result of snow leakage) inside the grain induced a hotspot development, which in turn influenced the grain temperature and moisture content. Germinability of the grain near the walls dropped later than those near the surface and inside the grain bulk, in the presence of insect infestation. The drop in ambient temperature could either cease the hotspot or lower the grain temperature. Highlights: Drop in ambient temperature can cease hotspot near the grain surface. Surface grain temperature and moisture fluctuate with changes in ambient condition. Hotspot development caused only by fungi, not by insect infestation. Developed hotspot did not lead to increase in grain moisture content.